MARTIAL ARTS TRAINING AND LEVELS OF ATTITUDE TOWARDS VIOLENCE IN ADOLESCENTS - Carlos Mª Tejero-González; Carlos Balsalobre-Fernández (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract Traditionally, japanesse martial arts had, as well as technical and tactical lessons, discourses of peace and non-violence. Therefore, this study wants to prove whether the practitioners of these martial arts declare lower levels of attitude toward violence than non-practitioners. To this end, we administered he Brief Scale of Violence in Adolescents (Tejero-González, Balsalobre-Fernández and Ibanez-Cano, in press) to two groups of boys and girls from 12 to 17 years of age: one group of judo, karate or jiujitsu (n = 57), and a control one (n = 57). Statistical analysis confirmed that martial arts practitioners declare significantly lower leves than the control group, both in general violence as gratuitous violence, but were not in violence linked to self-protection. Finally, we discuss the influence that factors such as years of practice or competitive orientation may have on the ability of the japanese martial arts to reduce levels of violence. Keywords: martial arts, judo, karate, jiujitsu, violence, adolescents.